Chemical Sciences in the Focus. - Adeniyi, Adeleke; Adeniyi, Adeleke; Adewuyi, Sheriff; Adewuyi, Sheriff; Amadou Condé, Sékou; Amadou Condé, Sékou; Amara Konaté, Ahmed; Amara Konaté, Ahmed; Canal, John P.; Canal, John P.; Chaichamni, Punnita; Chaichamni, Punnita; et al. (Chemical Sciences in the Focus, 2021)
Based on "The Virtual Conference on Chemistry and its Applications (VCCA-2020) - Research and Innovations in Chemical Sciences: Paving the Way Forward" held in August 2020 and organized by the Computational Chemistry Group of the University of Mauritius. The chapters reflect a wide range of fundamental and applied research in the chemical sciences and interdisciplinary subjects.